Freedom as a social value in the context of globalization (Journal of Philosophy Culture and Political Science, 2018)
In this article, the authors analyze such social values as freedom. Despite the fact that it enshrines one of the basic values of modern society, it is limited for a number of reasons. One of them is the economic sphere of society. The necessity of finding a livelihood causes the person to limit their actions, and interact with different social institutions and people. Therefore, one of the forms of freedom in modern society is called privacy. Privacy is the ability of the confidentiality of some aspects of his life. At the same time, deprived of the privacy of those individuals who break the rules of life in society. There is a direct relationship between the level of consumption and financial wellbeing and freedom. In the conditions of globalization freedom of movement for some is a blessing, for others – a forced measure. Also, the authors emphasize that you need a positive reflection on the process of globalization. Often globalization is understood in a negative sense as the unification of cultures. But do not forget about the fact that globalization has and exchange, giving the opportunity for further growth.Key words: social value, freedom, modern society, privacy, globalization